The Emerging Nano-Corporate Paradigm: Nanotechnology and the Transformation of Nature, Food and Agri-Food Systems - Scrinis, Gyorgy; Lyons, Kristen (The International Journal of Sociology of Agriculture and Food, 2007)
Nanotechnology represents the latest in a line of technological innovations set to transform agriculture and food production. From the farm to the table, nanotechnology research and development is being applied across the entire agri-food system. In this paper we outline the contours of what we call the nano-corporate food paradigm. We examine research and commercial applications of nanotechnology in the agriculture and food sectors, and showcase the ways in which the nano-corporate food paradigm is being applied, and at the same time may shape and transform agri-food systems.